2015
DOI: 10.1097/bot.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Complex Osteotomies of Tibial Plateau Malunions Using Computer-Assisted Planning and Patient-Specific Surgical Guides

Abstract: The accurate reduction of tibial plateau malunions can be challenging without guidance. In this work, we report on a novel technique that combines 3-dimensional computer-assisted planning with patient-specific surgical guides for improving reliability and accuracy of complex intraarticular corrective osteotomies. Preoperative planning based on 3-dimensional bone models was performed to simulate fragment mobilization and reduction in 3 cases. Surgical implementation of the preoperative plan using patient-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 44 publications
1
62
0
1
Order By: Relevance
“…Avoiding intraoperative imaging is a key advantage of the reduction guide system described here as well as similar CAD‐designed, 3D‐printed patient‐specific guide systems recently described in the treatment of human radial, tibial, and scaphoid fracture malunions. In those reports, advantages also included accurate restoration of bone conformation, simplified surgical technique, and potentially reduced surgical time . Good guide fit is a key determinant of the overall accuracy of such systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avoiding intraoperative imaging is a key advantage of the reduction guide system described here as well as similar CAD‐designed, 3D‐printed patient‐specific guide systems recently described in the treatment of human radial, tibial, and scaphoid fracture malunions. In those reports, advantages also included accurate restoration of bone conformation, simplified surgical technique, and potentially reduced surgical time . Good guide fit is a key determinant of the overall accuracy of such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports describe the use of a 3D‐printed patient‐specific drill guide for placement of bicortical pedicle screws in a canine cervical vertebra . Reports in the human literature detail the use of 3D‐printed patient‐specific osteotomy and reduction guides in the treatment of radial, tibial, and scaphoid fracture malunions . These techniques may facilitate closed, indirect fracture reduction and fracture alignment during MIPO but are as yet unreported in veterinary or human literature.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies reported satisfactory immediate surgical results (60-100%). Complication reporting was sparse with two exceptions: (i) van Steenberghe et al who reported 6/27 cases of bruxism (involuntary grinding of the teeth), a complication known to be associated with immediate loading of implants in fully endentulous maxillae [50], and (ii) F€ urnstahl et al [10] who describe severe pain postoperatively due to incomplete procedure [medial compartment of the knee not repaired in theatre, despite having achieved repair during rehearsal]. The number of participants was too small (n ¼ 3) to embark on further analysis ( Table 2).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…fusion of 2D-into 3D-images using computed tomography (CT) slides), and rapid prototyping (building a physical model using computer aided design (CAD) software, e.g. 3D printing) facilitate the effective and accurate construction of patient-specific anatomical models, surgical guides and implants [7][8][9][10], thus opening new avenues for pre-operative rehearsals.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical use of patient‐specific three‐dimensional (3D)‐printed osteotomy and reduction guide systems has been reported in human surgery in the correction of fracture malunions and other deformities . These guide systems are easier to use and less expensive than computer navigation systems, provide flexibility because of their custom‐design, reduce surgical time, and are significantly more accurate in terms of residual angulation and rotation compared with computer navigation systems or conventional freehand techniques .…”
Section: Introductionmentioning
confidence: 99%